A qualitative study exploring how school and community environments shape the food choices of adolescents with overweight/obesity. (1st December 2015) - Watts, Allison W.; Lovato, Chris Y.; Barr, Susan I.; Hanning, Rhona M.; Mâsse, Louise C.
Abstract: This study explored perceived barriers and facilitators to healthful eating in schools and communities among overweight teens who completed an E-health intervention. Twenty-two teens were recruited to a photovoice study and asked to take pictures of things that made it easier or harder to make healthful food choices at school and in their community. Digital photographs were reviewed using semi-structured interviews. Transcribed audio-recordings were analyzed using constant comparative analysis. Similar themes emerged from the school and community environments with food/beverage availability emerging most frequently, followed by peer influence, accessibility/convenience, price, classroom practices, marketing and online influences. Teens described an obesity-promoting environment and perceived very limited healthful options. Policy-driven environmental changes as well as strategies that help teens navigate food choices in their schools and communities are needed to support healthful eating. Highlights: Teens with overweight/obesity described an obesity-promoting environment. Teens perceived very limited healthful options at school and in the community. Policy-driven environmental changes may help to promote healthful eating. Interventions are needed that target socio-environmental influences on diet across settings.